Design and Evaluation of an Android-Based Educational Game to Support Animal Recognition Learning for Early Childhood at TK Aisyiyah 03 - Nurul Alfiah; Fadillah Istiqomah; Nisa Salsyabila (Blend Sains Jurnal Teknik, 2025)
Instilling basic knowledge during early childhood is a critical foundation for the development of cognitive, social, and emotional abilities. To support this developmental stage, learning media must not only be informative but also engaging and interactive, reflecting the unique characteristics of how young children learn. One key subject at the kindergarten level is animal recognition, which includes identifying animal names, sounds, shapes, and habitats. However, conventional teaching methods often struggle to maintain children’s attention, resulting in reduced focus and limited learning outcomes. To address this issue, the present study developed an Android-based educational game specifically designed to support animal recognition learning at TK Aisyiyah 03. This initiative applies the Research and Development (R&D) method, utilizing the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The resulting application features a variety of animals presented through appealing visuals, suitable sound effects, and interactive quizzes that aim to reinforce children's comprehension. The interface is carefully designed to align with the cognitive and motor skills of 4–5-year-old children, enabling both independent use and teacher-guided instruction. Trial implementation involving 15 students demonstrated that the educational game effectively increased interest, active participation, and understanding of animal names and characteristics. Students showed high levels of enthusiasm and responded positively to the learning process. Additionally, validation by content and media experts indicated the application's high feasibility, with an average score exceeding 85% for content, appearance, and interactivity. Further findings reveal the game's ability to enhance learning effectiveness, as evidenced by improvements in students’ evaluation results from pre-test to post-test. Teachers and students also gave positive feedback regarding the game as a learning medium. By incorporating the principle of "learning through play," the application addresses the limitations of conventional media, offering a more interactive and enjoyable learning experience. In terms of practicality, the game is easy to implement in classroom settings, being compatible with commonly available mobile devices and operable offline after download, thus requiring no internet connection.